2005
DOI: 10.1108/13620430510598328
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the career satisfaction of older managerial and professional women

Abstract: Article information:To cite this document: Marjorie Armstrong-Stassen Sheila Cameron, (2005),"Factors related to the career satisfaction of older managerial and professional women", Career Development International, Vol. 10 Iss 3 pp. 203 -215 Permanent link to this document: http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 30 publications
7
29
1
Order By: Relevance
“…For example, a review of the literature showed the association between education and career satisfaction levels to be ambiguous (Wayne et al, 1999;Seibert and Kraimer, 2001;Emmerik et al, 2006). In addition, employees with shorter tenure were found to be significantly more satisfied with their careers than employees with longer tenure (Judge et al, 1995;Hochwarter et al, 2004;Armstrong-Stassen and Cameron, 2005).…”
Section: Literature Reviewmentioning
confidence: 93%
See 2 more Smart Citations
“…For example, a review of the literature showed the association between education and career satisfaction levels to be ambiguous (Wayne et al, 1999;Seibert and Kraimer, 2001;Emmerik et al, 2006). In addition, employees with shorter tenure were found to be significantly more satisfied with their careers than employees with longer tenure (Judge et al, 1995;Hochwarter et al, 2004;Armstrong-Stassen and Cameron, 2005).…”
Section: Literature Reviewmentioning
confidence: 93%
“…Significant demographic control measures to examine include: age (Cox and Nkomo, 1991;Schneer and Reitman, 1994;Judge et al, 1995;Richardsen, Mikkelsen and Burke, 1997;Armstrong-Stassen and Cameron, 2005) and gender (Greenhaus, Parasuraman and Wormley, 1990;Igbaria, 1991;Schneer and Reitman, 1994;Burke, 2001;Seibert and Kraimer, 2001;Poon, 2004). Also, in light of Canada's most recent demographic information, Canadian born and foreign-born variables will also be examined.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The two terms 'subjective career success' and 'career satisfaction' can be used synonymously because they emphasize on individual's subjective evaluation of his or her career (Hofmans, Dries & Pepermans, 2008). OCM and ICM enhance employees' career satisfaction (Armstrong-Stassen & Cameron, 2005;King, 2004;Kong et al, 2012b). The organizations should improve employees' career satisfaction so as they could retain their employees (Hagiwara, Hasegawa, Chiba & Watase, 2014).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 99%
“…Growth in female employment in the professional and managerial fields has been substantial (Cabrera, 2007) and women now routinely continue in their careers into their 50s and beyond. Yet little is known about their late-career phase (Armstrong-Stassen and Cameron, 2005;August, 2011). Women's careers research has largely focused upon younger women and their challenges in combining career with childbearing and domestic responsibilities (for example, Crompton et al, 2005).…”
Section: Introductionmentioning
confidence: 99%